Addressing Occupational Fatigue in Nurses: A User-Centered Design Approach for Fatigue Risk Management. (March 2022) - Steege, Linsey M.; Arsenault Knudsen, Élise N.; Brzozowski, Sarah; Cho, Hyeonmi
Abstract : OBJECTIVE: To understand hospital nurses' current fatigue risk management (FRM), identify design goals and principles, and obtain feedback on FRM design concepts. BACKGROUND: FRM systems can address fatigue and associated risks, yet they are not widely implemented in hospital nursing. This may be due to a lack of contextually appropriate FRM tools. METHODS: A user-centered design approach was used, including interviews with 21 hospital nursing stakeholders. FINDINGS: Nurses described integrated fatigue monitoring and management activities to pursue balance between work demands and capacity to meet those demands as individual nurses, within the unit, across the hospital, and over time. Seven principles were identified and applied to 2 initial design concepts for tools to support FRM. Participants' feedback on designs was positive. CONCLUSIONS: This study advances the science and practice for FRM in nursing. The design principles and concepts from this study can be used to facilitate implementation of FRM systems in hospitals.